\(4x\left(3-\dfrac{1}{4}x\right)+\left(x-2\right)\left(x+2\right)=0\)
\(\Rightarrow12x-x^2+x^2-4=0\Rightarrow12x=4\Rightarrow x=\dfrac{1}{3}\)
\(12x-x^2+x^2-2^2=0\)
\(12x-2=0\)
\(12x=2\)
\(x=\dfrac{1}{6}\)
Vậy x=1/6
\(4x\left(3-\dfrac{1}{4}x\right)+\left(x-2\right)\left(x+2\right)=0\)
\(\Rightarrow12x-x^2+x^2-4=0\Rightarrow12x=4\Rightarrow x=\dfrac{1}{3}\)
\(12x-x^2+x^2-2^2=0\)
\(12x-2=0\)
\(12x=2\)
\(x=\dfrac{1}{6}\)
Vậy x=1/6
Tìm x : a) x^3 - 1/4x = 0 b) ( 2x - 1 )^2 - ( x + 3 )^2=0 c) x^2(x-3)+12-4x=0
tìm x biết
a)4x^2+4x-3=0
b)x^4-3x^3-x+3=0
c)x^2(x-1)-4x^2+8x-4=0
tìm x biết
a)4x^2+4x-3=0
b)x^4-3x^3-x+3=0
c)x^2(x-1)-4x^2+8x-4=0
Tìm x
x^2 - 4x = 0
4x^2 - 9 = 0
2x ( x - 3 ) + 5( x - 3 ) = 0
x ( 2x + 9 )- 4x - 18
( 2x - 1 )^2 - ( x + 2 )^2 = 0
Tìm x biết:
a) \(3x^2-4x=0\). b) \(\left(x+3\right)\left(x-1\right)+2x\left(x+3\right)=0\).
c) \(9x^2+6x+1=0\). d) \(x^2-4x=4\).
Tìm x
a) (x + 3)2 + (x + 2)(5 – x) = 1
b/ (2x – 1)2 – ( x – 5)( 4x + 3) = 3
c/ 3x (x – 2) + 4x – 8 = 0
d/ 2x (3x + 5) – 18x – 30 = 0
Tìm x
x^2 - 4x - 12 = 0
4x^2 + 4x - 24 = 0
8x^3 - 12x^2 + 6x - 1 = 0
A= 1/x+2 - x^3-4x/x^2+4 .(1/x^2+4x+4 +1/4-x^2) a) tìm TXĐ,R/G A b) x=? để A>0;A<0;A=0 GIÚP MIK VS MIK ĐAG CẦN GẤP
tìm x biết
1, x mũ 3 + 4x mũ 2 + 4x = 0
2, ( x + 3 ) mũ 2 - 4 = 0
3, x mũ 4 - 9x mũ 2 = 0
4, x mũ 2 - 6x + 9 = 81
5, x mũ 3 + 6x mũ 2 + 9x - 4x = 0